Improving the Productivity of Laying Hens Through a Modern Cage Cleanliness Monitoring System that Utilizes Integrated Sensors and IoT Technology - Ishak, Fauzi; Wardhana, Ichlasul Amal Restu; Mutiara, Giva Andriana; Periyadi, Periyadi; Meisaroh, Lisda; Alfarisi, Muhammad Rizqi (Universitas Muhammadiyah Yogyakarta, 2024)
Animal husbandry plays a crucial role in the Indonesian economy. One example is layer farming. The cage's environmental conditions can have an impact on the health of laying hens, including factors like temperature, humidity, and the presence of ammonia gas. This research aims to support chicken farmers in identifying and monitoring the environmental conditions surrounding their chicken coops, with the goal of enhancing the productivity of laying hens. This study is organized using a prototype development approach. The proposed system utilizes Arduino UNO as a microcontroller, ESP32 as a connecting node from hardware to software, MQ-135 sensor as an ammonia gas sensor, DHT-22 sensor as a temperature and humidity sensor, and 16x2 I2C LCD to display the collected data. WIFI connected web monitoring system built with Laravel, MySQL, and Bootstrap. An improvement to the existing system is the integration of an ammonia gas odor sensor calibrated against clean air as a reference. Testing was conducted for a continuous period of 7 days. Comparison of test results is performed with existing devices to observe the difference in measured values. The measurement result demonstrates a remarkable ability to accurately measure temperature, humidity, and ammonia levels in the air. The difference with the comparable device was about 2%. Meanwhile, the monitoring dashboard for IoT functional monitoring operates effectively, allowing chicken farmers to efficiently analyze the cleanliness of their chicken coops. All measurement parameters are conveniently recorded in the form of tables and graphs, providing valuable information.